Workshop Penggunaan Kartu Operasi Hitung Untuk Pembelajaran Materi Perkalian Faktor di SD Negeri Inpres Skouw Mabo, Jayapura - Lidwina C. Maniboey; Aisyah Ali; Suwita Suwita; Siti Mudrikah (LPPM Uncen, 2025)
This study aimed to optimize instruction in basic multiplication (multiplication of factors) at SDN Inpres Skouw Mabo, a public primary school located in the Indonesia–Papua New Guinea border area, through the use of Kartu Operasi Hitung (Arithmetic Operation Cards). The school has faced persistent challenges in addressing students’ difficulties with multiplication, which is a foundational concept in mathematics. Limited facilities and instructional resources have impeded the attainment of optimal understanding. Therefore, the introduction of a simple instructional manipulative - Arithmetic Operation Cards - was proposed to support a more visual and interactive learning process. The intervention consisted of teacher training on the use of the cards within mathematics lessons. The training covered both theoretical underpinnings and practical classroom strategies. Furthermore, direct classroom observations were conducted to evaluate the implementation of the manipulative and its influence on students’ understanding. The training and subsequent classroom implementation were expected to improve students’ understanding of multiplication and to strengthen their engagement with the learning process. Overall, these activities were intended to contribute positively to the quality of mathematics instruction at SDN Inpres Skouw Mabo. Moreover, the approach may inform the development of more interactive and enjoyable pedagogical methods and might contribute to efforts to enhance educational quality in border regions that often confront constraints in access and resources.